The competence of an arbitral tribunal under the Convention on the Settlement of Investment Disputes between States and Nationals of other States : an analysis of bilateral investment treaties provisions and a question of admissibility - Rey de Castro Alarco, Álvaro Santiago (2007)
The International Centre for Settlement of Investment Disputes (hereinafter IC-SID) was established by the Convention on the Settlement of Investment Disputes between States and Nationals of Other States (hereinafter ICSID Convention or Washington Convention). The Convention came into force the 14th of October of 1966. ICSID’s role, according to the Washington Convention, is to provide facilities for conciliation and arbitration of investment disputes between Contracting States and nationals of Other Contracting States. In the present article, we will focus on arbitration under the convention and particularly on the jurisdiction of an arbitral tribunal constituted under the mentioned international instrument.